Combine harvester subsidies and agricultural mechanization in Bangladesh: Recommendations for reform - Bakhtiar, M. Mehrab; Mahzab, Moogdho; Karim, Md. Aminul; Shamma, Raisa; Belton, Ben; Talukder, Md. Ruhul Amin; Kabir, Razin; Aravindakshan, Sreejith; Krupnik, Timothy J.; Ahmed, Akhter (International Food Policy Research Institute, 2025)
This brief summarizes findings from a recent report1 on Bangladesh's Phase III agricultural mechanization support program (2020–2024). The program distributed over 35,000 subsidized machines worth BDT 1,595 crore (USD 163 million). Combine harvesters (CHs) accounted for 84% of program value, making them the focus of this analysis. Drawing on administrative data, a survey of 979 Machinery Service Providers (including 400 CH MSPs), panel data from over 2,000 Boro rice-producing households, and 128 qualitative interviews, the report examines program impacts and identifies critical implementation gaps.